PERKAWINAN MARGA HUKUL DI DESA LARIKE - Yusup Laisouw (IAIN Ambon, 2019)
ABSTRACT According to Islamic law marriage is a sacred (sacred) agreement based on religion between husband and wife based on religious law to achieve one intention, one goal, one effort, one right, one obligation, one feeling: living as semati. Marriage According to Customary Law is one of the most important events in the lives of indigenous people. In the tradition of the Marga Hukul, only girls with the surname Hukul carry out marriages using traditional clothes that have been set during the time of the special occasion. In this bidding also, the women carried out custom in the form of prior notice to the elders of the country (their ancestors on the mountain) asking for their willingness to attend the event, this was also called the custom of mountaineering. After the women stated the mountain customs, the men began to prepare themselves and will be delivered as soon as possible to the women to carry out the custom of the mountain. For the villagers of Larika, the traditional ceremony of the Hukul clan is very sacred and has its own meaning. The level of sacredness is in the customary provisions that have been valid since ancient times until now. ABSTRAK Menurut hukum Islam perkawinan adalah perjanjian suci (sakral) berdasarkan agama antara suami dengan istri berdasarkan hukum agama untuk mencapai satu niat, satu tujuan, satu usaha, satu hak, satu kewajiban, satu perasaan: sehidup semati. Perkawinan Menurut Hukum Adat adalah salah satu peristiwa yang sangat penting dalam kehidupan masyarakat adat. Dalam tradisi Marga Hukul, hanyalah anak perempuan yang bermarga Hukul yang melakukan perkawinan dengan menggunakan baju adat yang telah ditetapkan pada masa peminangan. Dalam peminangan ini juga, pihak perempuan melakukan adat yang berupa pemberitahuan terdahulu kepada orang tua-tua negeri (nenek moyang yang ada di gunung) meminta kesediaan mereka untuk hadir dalam acara peminangan itu, ini disebut juga dengan melakukan adat gunung. Setelah pihak perempuan menyatakan adat-adat gunung tersebut, pihak laki-laki mulai mempersiapkan diri dan akan diantarkan secepatnya kepada pihak perempuan untuk melaksanakan adat gunung tersebut. Bagi masyarakat desa Larika upacara adat perkawinan marga Hukul sangat sakral dan memiliki makna tersendiri. Tingkat kesakralan itu berada pada ketentuan adat yang berlaku sejak jaman dahulu hingga sekarang. Kata kunci : perkawinan, adat, hukum adat